Internalizing Religious Moderation through Qur’an and Hadith Learning: A Case Study in Indonesian Madrasah Ibtidaiyah - Hasanah, Intan Andriani; Hayati, Lutfiah Isfa (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2025)
The growing need to strengthen religious moderation in Qur’an and Hadith learning requires contextual strategies that support character formation. This study aims to describe how teachers in Madrasah Ibtidaiyah internalize moderation values and shape students’ moderate character. Using a qualitative case study design, data were collected through observations, in-depth interviews, and documentation, then analyzed thematically with validation ensured through source and technique triangulation. The findings show that teachers integrate values such as tolerance, justice, courtesy, and balanced religious understanding through relevant Qur’anic verses and hadiths, discussion-based activities that build critical thinking, and the use of interactive media. These values are reflected not only in students’ cognitive understanding but also in behaviors such as respecting differences, fairness, kindness, discipline, and responsibility. This study addresses gaps in previous research, which has been mainly theoretical, and provides practical implications for developing contextual Qur’an–Hadith learning models grounded in moderation principles.